Pemahaman Manajemen Dalam Kelancaran Proses Pencatatan Laporan Keuangan Perusahaan Jasa Advertising - Anisyah Rahmadani; Menur Kusumaningtyas (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Research in this internship program was carried out to find out the company's work activities resulting in a fairly large turnover and the process of recording financial reports in companies engaged in advertising and stamp making services in Surabaya. The performance of the sales and marketing team as well as the management team has an important role in the process of recording financial reports and the expected stability of turnover. Recording financial reports must involve all necessary activities and aims to serve as an information medium for management to plan and control and report on the company's conditions and operations. Companies need financial reports to evaluate financial performance for stakeholders who need this information. The more balanced the relationship between individual and group performance, the better the value of the company's performance. This business process which operates in the field of advertising and stamp making services in the current era is very popular and is needed by corporate agencies and individuals to introduce their business to the public. Forms in this advertising creation service can include neon boxes, embossed letters, banners and stamps. The management system plays a very important role in this advertising business.